The History of UNCTAD, 1964-1984 - UNCTAD; United Nations Conference on Trade and Development (New York : United Nations, 1985)
This book, prepared to mark the twentieth anniversary of UNCTAD,attempts to portray and assess the achievements of the Organization.
"UNCTAD/OSG/286"--T.p. verso.
"United Nations publication. Sales no. E.85.II.D6"--T.p. verso.
Includes bibliographical references.
II 16/01/2019
Loans